Circulating microparticle concentrations across acute and chronic cardiovascular disease conditions. Issue 15 (3rd August 2020) - Landers‐Ramos, Rian Q.; Addison, Odessa A.; Beamer, Brock; Katzel, Leslie I.; Blumenthal, Jacob B.; Robinson, Shawn; Hagberg, James M.; Prior, Steven J.
Abstract: Concentrations of different circulating microparticles (MPs) may have clinical and physiological relevance to cardiovascular disease pathologies. Purpose: To quantify plasma concentrations of CD31+/CD42b−, CD62E+, and CD34+ MPs across healthy individuals and those with coronary artery disease (CAD) or acute cardiovascular events (non‐ST elevation myocardial infarction (NSTEMI)). Fasted blood was obtained from CAD patients ( n = 10), NSTEMI patients ( n = 13), and healthy older men ( n = 15) 60–75 years old. Methods: CD31+/CD42b−, CD62E+, and CD34+ MPs were isolated from plasma and quantified using flow cytometry. Relationships between MP subtypes, fasting blood lipids, blood glucose, blood pressure, body mass index, and total number of medications were assessed. Results: Concentrations of CD31+/CD42b− MPs were significantly lower in CAD and NSTEMI subjects compared with healthy individuals ( p = .02 and .003, respectively). No differences between groups were found for CD62E+ or CD34+ MPs ( p > .05 for both). Surprisingly, among all variables assessed, only CD62E+ MP concentrations were positively correlated with triglyceride levels ( p = .012) and inversely correlated with SBP ( p = .03). Conclusions: Our findings provide support for the use of different MP subtypes, specifically CD31+/CD42b− MPs, as a potential biomarker of cardiovascular disease. Importantly, results from this study should be looked at in adjunct to previous MP work in CVD conditions as a way of highlighting the complex interactions of variables such as comorbid conditions and medications on MP concentrations. Abstract : In contrast to CD62E+ and CD34+ MPs, CD31+/CD42b− MPs were significantly lower in CAD and NSTEMI patients versus healthy older adults. These findings suggest CD31+/CD42b− MP concentration as a potential biomarker of cardiovascular disease and highlight the need for a better understanding of comorbidities and medications on MP concentrations.